Sử dụng hàm trọng lượng - tuyến nhằm tăng cường độ phân giải trong phân tích tài liệu từ và trọng lực bằng phép biến đổi Wavelet - Liệt, Đặng Văn; Toàn, Lương Phước; Đẩu, Dương Hiếu (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Using the line-weight function to enhance the resolution of gravity and magnetic data in interpretation by Wavelet transform The multiscale edge detection (MED) using wavelet transform was used to solve the inversion problem of gravity and geomagnetism to determine the positions and the depths of sources. In this paper, we used the line-weight function (LWF) to treat the observational data to enhance the resolution of the results of MED method. Firstly, the method was applied on the theoretical gravity model and the magnetic experimental model to prove the reliability of method. Secondly, the method was used to interpret the magnetic profile in Mekong delta area as well. The results showed thatthis method can determine not only the positions and the depths but also the widths, the thickness and the dip of the sources. The determination of these source parameters is the special achievement of this method comparing with other methods.